Increased risk of lung cancer in individuals with preserved ratio impaired spirometry: a nationwide cohort study - Taeyun Kim; Junsu Choe; Yunjoo Im; Jihye Heo; Hye Yun Park; Danbee Kang; Sun Hye Shin (Scientific Reports)
Abstract Accumulating data showed that individuals with preserved ratio impaired spirometry (PRISm) have an increased risk for all-cause mortality and respiratory-related mortality compared with normal spirometry. However, the association between PRISm and lung cancer development is not known. A retrospective cohort study was conducted using the Korean National Health and Nutrition Examination Survey data between 2007 and 2017, which was linked to the Health Insurance Review and Assessment database from 2007 to 2021. Men and women aged 40 to 79 years were categorized by baseline spirometry; PRISm (FEV1/FVC ≥ 0.7 and FEV1 < 80% pred), COPD (FEV1/FVC < 0.7) and normal spirometry (FEV1/FVC ≥ 0.7 and both FEV1 and FVC ≥ 80% pred). Incident lung cancer was defined as the presence of the International Classification of Diseases-10 C33 or C34 code. Among 26,490 individuals, 2628 (9.9%) and 3811 (14.4%) had PRISm and COPD, respectively. Compared to those with normal spirometry, those with PRISm were more likely female (72.0%) and never-smokers (70.2%). During the median follow-up of 10 years, individuals with PRISm (fully-adjusted HR = 1.83, 95% CI 1.25, 2.66) and COPD (fully-adjusted HR = 2.91, 95% CI 2.23, 3.80) had significantly higher risk of lung cancer than those with normal spirometry. The association between PRISm and lung cancer was more evident in ever smokers. This nationwide cohort study revealed that PRISm might be an independent risk factor for lung cancer development.